Light scattering reviews 9 : light scattering and radiative transfer - Kokhanovsky, Alexander A. (Springer Praxis Books, 2015)
Light Scattering Reviews (vol.9) is aimed at the description of modern advances in radiative transfer and light scattering. The following topics will be considered: light scattering by atmospheric dust particles and also  by inhomogeneous scatterers, the general - purpose discrete - ordinate algorithm DISORT for radiative transfer, the radiative transfer code RAY based on the adding-doubling solution of the radiative transfer equation, aerosol and cloud  remote sensing, use of polarization in remote sensing, direct aerosol radiative forcing, principles of the Mueller matrix measurements, light reflectance from  various land surfaces. This volume will be a valuable addition to already published volumes 1-8 of Light Scattering Reviews.